Advection by ocean currents modifies phytoplankton size structure - Font-Muñoz, Joan S. (J R Soc Interface, 2017)
Advection by ocean currents modifies phytoplankton size structure at small scales (1–10 cm) by aggregating cells in different regions of the flow depending on their size. This effect is caused by the inertia of the cells relative to the displaced fluid. It is considered that, at larger scales (greater than or equal to 1 km), biological processes regulate the heterogeneity in size structure. Here, we provide observational evidence of heterogeneity in phytoplankton size structure driven by ocean currents at relatively large scales (1–10 km). Our results reveal changes in the phytoplankton size distribution associated with the coastal circulation patterns. A numerical model that incorporates the inertial properties of phytoplankton confirms the role of advection on the distribution of phytoplankton according to their size except in areas with enhanced nutrient inputs where phytoplankton dynamics is ruled by other processes. The observed preferential concentration mechanism has important ecological consequences that range from the phytoplankton level to the whole ecosystem.